Significant Global Yield-Gap Closing Is Possible Without Increasing the Intensity of Environmentally Harmful Nitrogen Losses - Smerald, Andrew; Fuchs, Kathrin; Kraus, David; Butterbach-Bahl, Klaus; Scheer, Clemens (Frontiers in Sustainable Food Systems, 2022)
Substantial increases in cereal yields are necessary if a growing global demand for food is to be met without further conversion of natural to agricultural land. However, since in many regions yields are limited by soil nutrient availability, this will increase the requirement for fertiliser inputs, specifically of nitrogen (N). Here we focus on maize cultivation, and investigate the trade-off between yield increases and environmentally harmful N-losses in the form of nitrous oxide (N2O) emissions and nitrate (NO3) leaching. In particular, we model the evolution of N-losses as yield gaps - the difference between actual and potential yields - are closed. To do this we use the process-based, biogeochemical model LandscapeDNDC to perform global simulations on a 0.5 degree grid, and evaluate the response of yields and environmental N-losses to changes in N-inputs. Our simulations find current production (circa 2015) of 954 Tg (5.1 Mg/ha), direct and indirect N2O emissions of 416 Gg-N (2.2 kg-N/ha or 0.44 kg-N/Mg) and NO3 leaching of 5.9 Tg-N (31.5 kg-N/ha or 6.2 kg-N/Mg). We demonstrate that, under an 'optimal' strategy for closing yield gaps, maize yields could be increased by 20-25% with concomitant stable or even slightly decreased yield-scaled N-losses. However, further yield increases would come at an ever accelerating cost in environmentally harmful N losses. This acceleration occurs when yields exceed approximately 70-80% of their potential.